Brassica rapa L. subsp. rapa NGB 5020 ... - GLIS Of The ITPGRFA (Nordgen, 2024)
Plant Genetic Resource. Taxonomy: Brassica rapa L. subsp. rapa Common name(s): BrassicaComplex, Brassica complex Other names: Målselvnepe Gibostad Stamme, MÅLSELVNEPE GIBOSTAD STAMME Conserved by: Nordgen (NORDGEN), Sweden Local sample unique identifier: NGB 5020 Method of creation: Acquisition Date: 1985-05-21 Historical: No Biological status: Advanced or improved cultivar MLS status: Included ...